Responsiveness of patient reported outcomes including fatigue, sleep quality, activity limitation, and quality of life following treatment with abatacept for rheumatoid arthritis. Issue 2 (10th September 2007) - Wells, G; Li, T; Maxwell, L; Maclean, R; Tugwell, P
Abstract : Objective: To evaluate the responsiveness of patient reported outcomes (PROs), including fatigue, sleep, activity limitation, and quality of life, in patients with rheumatoid arthritis (RA). Methods: Data were considered from a randomised controlled trial comparing abatacept (n = 258) with placebo (n = 133) on a background of DMARD treatment in RA patients who were inadequate responders to anti-TNF therapy (ATTAIN study). PROs assessed included SF-36, activity limitation, fatigue, and sleep. For each outcome the treatment difference, relative per cent improvement, standardised response mean (SRM), and relative efficiency for assessing an outcome's ability to detect a treatment effect relative to tender joint count (TJC) were calculated. A relative efficiency >1 suggests a measure that is more efficient than TJC in detecting treatment effect. Results: Moderate to large SRMs (⩾0.6) were observed for the PRO measures. In particular, SRMs (95% confidence interval) were: physician global, 0.72 (0.51 to 0.94); HAQ, 0.63 (0.42 to 0.85); SF-36 physical component score, 0.62 (0.40 to 0.83); SF-36 bodily pain, 0.68 (0.46 to 0.90); and fatigue, 0.59 (0.38 to 0.81). Relative efficiencies for physician global (1.6), SF-36 bodily pain domain (1.4), pain intensity (1.4), HAQ (1.2), SF-36 physical component score (1.2), fatigue (1.1), and patient global assessment (1.04) were all more responsive than TJC. The SF-36 mental component score (0.3), swollen joint count (0.6), activity limitation (0.8), sleep (0.7), and C reactive protein (0.9) were less responsive. Conclusions: Using PROs for evaluating treatments for RA can detect improvements and will identify changes that are important to patients. In general, physical assessments are more responsive to an effective treatment than mental assessments.